The Exploration of Verbal and Visual Signs with Reference to BTS Music Video “Dynamite” and Its Song Lyrics - Dwi Permata Sari, Ni Kadek (Udayana Journal of Social Sciences and Humanities; Vol 8 No 1 (2024): Vol 8 No 1 (2024): UJoSSH, Februari 2024DO - 10.24843/UJoSSH.2024.v08.i01.p06, 2024)
This study entitled The Exploration of Verbal and Visual Signs with Reference to BTS Music Video “Dynamite” and Its Song Lyrics. There were three aims of this study; explaining the meaning of verbal signs, describing the meanings of visual signs and analyzing the relation between verbal and visual signs on the Dynamite song and its music video. The data were taken from an English song by BTS ( Bangtan Seonyondan) that was released on 21 st August 2020. The data was limited on the second chorus of the song and the 8 th scene of the music video. The data was gathered from the music video by watching the music video through YouTube and reading the song lyrics that was found in search engine. The collected data from this study was analyzed using the qualitative method. Then, the data was analyzed with semiotic theory by Charles Sanders Pierce and seven types of meaning theory by Geoffrey Leech and also supported by other theories and opinions from numerous experts in this field. There were two out of seven types of meaning found in Dynamite song lyrics—second chorus part. The types of meaning were conceptual meaning and connotative meaning. there were also their visual signs that categorized as icon, index, symbol was found in the 8 th scene of the music video. In this study was also found the relation between the verbal and visual signs of Dynamite’s lyrics and its music video.